Advantageous Extraction, Cleanup, and UHPLC-MS/MS Detection of Patulin Mycotoxin in Dietary Supplements and Herbal Blends Containing Hawberry from Crataegus spp. - Anna Przybylska; Grzegorz Bazylak; Robert Kosicki; Iwona Altyn; Magdalena Twaruzek; Jan Grajewski; Anna Soltys-Lelek (Journal of Analytical Methods in Chemistry)
Patulin (PAT) is a highly genotoxic mycotoxin still found as the common contaminant of various kinds of spoiled fruits and related commodities which are often endorsed as the health-enhancing products. Thus, a fast and convenient liquid-solid extraction followed by a solid-phase cleanup with the MycoSep®228 AflaPat multifunctional column was used for the highly efficient isolation of PAT with an average recovery of 112.7% from commercial dietary supplements and herbal blends formulated with dried hawberry. Analysis of the PAT content was carried out using gradient elution with a Synergi Polar C18 column (150 × 2 mm, 4 μm) and UHPLC system equipped with a mass spectrometer. PAT was detected in all (n=14) commercial single-component dietary supplements formulated with dried hawberry belonging to Crataegus monogyna and/or Crataegus laevigata. Similarly, PAT was detected in 67% of the studied multicomponent commercial herbal blends (n=6) that contained—in addition to hawberry—different amounts of apple, chokeberry, elderberry, hibiscus, or mallow. Moreover, the PAT content was determined in the hawberry collected from the mature wild hawthorn trees belonging to three botanical species, Crataegus monogyna Jacq., Crataegus laevigata (Poiret) DC, and Crataegus rhipidophylla Gand, growing in the recreational forest areas and in the law-protected state national forest park in Poland. In conclusion, to prevent PAT accumulation and reduce the health risk of consumers in globalizing markets, the implementation of improved cultivation/processing practices of hawthorn trees and hawberry as well as increased analytical control related to the presence of PAT in dietary supplements and herbal blends formulated with fresh, dried, or frozen hawberry should be urgently recommended.